1976
DOI: 10.1172/jci108367
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of production of intestinal secretion by elevated venous pressure.

Abstract: A B S T R A C T A study was carried out to elucidate the physiological mechanisms responsible for the intestinal secretion produced by venous pressure elevation. In dogs, measurements were made of the rate and composition of small intestinal secretion, rate of flow and composition of intestinal lymph, plasma composition, and mucosal water content, all in response to elevations of intestinal venous pressure. Venous pressure elevations above a threshold value of 30-35 cm H20 produce secretion at a rate approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

1978
1978
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 32 publications
(35 reference statements)
3
24
0
1
Order By: Relevance
“…The mechanism of protein loss in the absence of ulceration is not clear. Obstruction of lymphatic flow by inflammation and fibrosis in the lamina propria may increase tissue fluid pressure, and it has been shown that increased tissue pressure changes the permeability of the intestinal epithelium allowing leakage of protein [25]. Fluid pressures within the mucosa would also be likely to increase due to activity of vasoactive amines produced during immediate hypersensitivity reactions as is said to occur in paratuberculosis in cattle [14].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of protein loss in the absence of ulceration is not clear. Obstruction of lymphatic flow by inflammation and fibrosis in the lamina propria may increase tissue fluid pressure, and it has been shown that increased tissue pressure changes the permeability of the intestinal epithelium allowing leakage of protein [25]. Fluid pressures within the mucosa would also be likely to increase due to activity of vasoactive amines produced during immediate hypersensitivity reactions as is said to occur in paratuberculosis in cattle [14].…”
Section: Discussionmentioning
confidence: 99%
“…The observed flux ratio is computed by (lumen-to-plasma flux):(plasma-to-lumen flux). The calculated flux ratio for passive ion movement is derived from the PD and ion concentration in plasma and lumen according to Ussing's equation (20). With limitations described in the text, a significant difference between observed and calculated flux ratio suggests active transport.…”
Section: Discussionmentioning
confidence: 99%
“…We have also examined histological sections and protein output to look for evidence of filtration as an additional cause of intestinal secretion (20)(21)(22) an electrical gradient for the passive secretion of cations, while development of a high concentration of ions at the site of secretion (within crypts or within villous unstirred layer) would promote osmotic flow of water from plasma to lumen. Inspection of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Lifson (14) showed in dogs that elevations of venous pressure as low as 4-6 cm H 2 O caused "secretory filtration" by both providing a driving force for secretion and increasing the hydraulic permeability of the epithelium, without which the driving force would be ineffective. The resulting pores, which are reminiscent of those induced by TNF and LIGHT, are large enough for proteins to pass.…”
Section: Figurementioning
confidence: 99%